The Novel Use of GLP-1 Analogue and Insulin Combination in Type 2 Diabetes Mellitus - P. Baruah, Manash; Kalra, Sanjay (Recent Patents on Endocrine, Metabolic & Immune Drug Discovery (Discontinued), 2012)
Type 2 diabetes mellitus (T2DM) is a global public health problem. Due to the progressive nature of the disease, a combination(s) of two or more drugs acting on different pathophysiological process is often necessary to achieve early and sustained achievement of individualized glycemic targets. At the same time, choosing the safest option to avoid hypoglycemia is of paramount importance. GLP-1 analogues are a relatively recent class of anti-diabetic drugs, and are highly effective with an acceptable safety profile. Attempts have been made to combine GLP-1 analogues with basal insulin for management of T2DM. Presently GLP-1 analogues like exenatide/long acting exenatide and liraglutide have been co-administered with basal insulin like glargine and detemir respectively, and are approved by regulatory agencies. Currently a fixed dose combination (FDC) of insulin degludec and liraglutide is under development. GLP-1 analogue and insulin as FDC or by co-administration, is a rational method of controlling fasting and postprandial glucose effectively. The efficacy and safety of this combination has been studied in a wide population with promising outcomes. Innovative use of GLP-1 analogues beyond diabetes is also being attempted, and a variety of patents are filed or granted for the same. This review summarizes the current status of GLP-1 and insulin combination in the management of T2DM and highlights the new frontiers in research involving GLP-1. Patents on combination of GLP-1 and insulin which were granted earlier, and the ones which have been applied for, are also discussed.
Keywords: hypoglycemia